Extraction and Characterization of Pectin from Red Hawthorn (Crataegus spp.) Using Citric Acid and Lemon Juice - Yarligan Uysal, Selma; Yildirim, Emre (Asian Journal of Chemistry, 2014)
A new generation of pectin was extracted from red hawthorn fruit. Pectin extraction was optimized by varying pH, temperature and time as well as the type of extraction solvents, i.e., lemon juice or citric acid. Accordingly, the maximum extracted yield of hawthorn pectin occured when extracted at pH 1.5/60 °C/120 min and pH 2.76/90 °C/120 min citric acid or lemon juice as an extraction solvent, respectively. Moreover, the characteristics measured at these optimized conditions are as follows: pectin yield 16.75 and 7.32 % of dry matter, anhydrouronic acid content 122.90 and 86.21 %, degree of esterification 54.16 and 53.34 % and acetyl groups 0.68 and 0.76 %, respectively. The optimum extraction condition ranges for obtaining desirable physico-chemical parameters of hawthorn pectin, were 60 and 90 °C for 120 min using acidic methods. Pectin obtained using both lemon juice and citric acid was a higher purity than commercial apple pectin.